New enchytraeid species (Enchytraeidae, Oligochaeta) from Korea - Dózsa-Farkas, Klára; Felföldi, Tamás; Hong, Yong (Zootaxa, 2015)
We give descriptions of five new enchytraeid species (Enchytraeidae, Oligochaeta) from Korea: Henlea magnaampullacea sp. n., Fridericia sphaerica sp. n., F. cusanicaformis sp. n., F. granulocyta sp. n. and Mesenchytraeus calyx sp. n., with morphological and molecular (mitochondrial cytochrome c oxidase subunit I, nuclear histone 3 genes and nuclear ribosomal ITS region sequences) data. In total, 19 enchytraeid species belonging to seven genera have been found in the studied woodland and agronomical soil samples. Apart from the five new species, three further species are new for the Korean enchytraeid fauna, Enchytraeus christenseni, E. dichaetus, and Achaeta cf. brevivasa. Molecular taxonomical analyses show that the Korean species resembling H. ventriculosa is not identical with the European species, furthermore sequence analysis of individuals morphologically identified as F. seoraksani indicate the possibility of species-complexity and the presence of cryptic species.